Customer satisfaction towards service quality and company image offered by Air Asia - Zuhairi, Aishah; Saad, Mazni (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh Campus, 2019)
Recently, the term satisfaction has been extensively used in tourism. In general, service provider sectors are striving to meet their customer’s satisfaction by delivering the best hospitality for their business. The importance of customer satisfaction can never be ignored especially when working in the tourism industry. In fact, delivering good customer service experience are essentials for most businesses especially service provider. World Tourism Organization has proposed to Governments to establish National Certification System for Sustainable Tourism and among the suggested criteria in the social indicator is a guest feedback system and customer satisfaction. Failure in delivering good customer service has brought so many negative impacts especially in terms of customer loyalty and sustainability of the businesses. The objective of this research is to point out the reactions on customer satisfaction regarding service quality and company image offered by Air Asia by using Parasuraman SERVQUAL Model. This study has highlighted four components of service quality which is, caring, reliability, tangibility, and responsiveness. The second objective is to recognize the significant issues that can influence the progression of customer satisfaction on Air Asia management and the last objective is to verify the important relationship of company image and services quality toward customer satisfaction of the Air Asia management. By understanding customer satisfaction, the authorities for the service provider in the tourism sector could take actions that will enhance local Airlines Industry image and brand as well as ensuring the sustainability of the business. The research will be conducted in Kuala Lumpur International Airport (KLIA), Sepang, Selangor.